2017
DOI: 10.3390/jfb8030033
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Responses to Total Hip Arthroplasty

Abstract: The use of total hip arthroplasties (THA) has been continuously rising to meet the demands of the increasingly ageing population. To date, this procedure has been highly successful in relieving pain and restoring the functionality of patients’ joints, and has significantly improved their quality of life. However, these implants are expected to eventually fail after 15–25 years in situ due to slow progressive inflammatory responses at the bone-implant interface. Such inflammatory responses are primarily mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 82 publications
0
33
0
Order By: Relevance
“…An analysis of total hip revision data from different arthroplasty registries from around the world ( 2 ) showed that the 10-year risk for revision can range from 0.6 up to 66.5% depending on the type of endoprosthetic implants used. The majority of revision surgeries are due to aseptic implant loosening ( 3 ), which is associated with a non-specific foreign body response to non-biological influences, such as wear particles or with mechanical problems like stress-shielding ( 4 ). The biologic reaction to wear particles consequently leads to the induction of osteolytic processes in the implant surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of total hip revision data from different arthroplasty registries from around the world ( 2 ) showed that the 10-year risk for revision can range from 0.6 up to 66.5% depending on the type of endoprosthetic implants used. The majority of revision surgeries are due to aseptic implant loosening ( 3 ), which is associated with a non-specific foreign body response to non-biological influences, such as wear particles or with mechanical problems like stress-shielding ( 4 ). The biologic reaction to wear particles consequently leads to the induction of osteolytic processes in the implant surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are a primary immune cell type and the main cellular type involved in inflammatory processes [ 1 ] and in host response [ 28 ], so their biologic host response to wear particles generated from the implanted materials is of great interest.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term survivorship of THA is limited by wear particle-induced osteolysis, in which the monocyte/macrophage lineage cells play a pivotal role. The biotoxicity, biocompatibility and mechanics properties had been greatly renovated with the regeneration of prosthesis materials, but the aseptic loosening caused by wear particles still remain unsolved [1]. Upon activation by wear particles, macrophages release a series of proinflammatory cytokine like TNF-α, IL-6 and IL-1β which induce the recruitment of macrophage and trigger the activation of osteoclast precursors [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…THA is a successful and widely used surgical procedure for the treatment of endstage degenerative and inflammatory osteoarthropathy. However, hip prosthesis only has an in-service life of 15-25 years, nearly all of the patients need to receive revision surgery in the end [1]. According to a complicationbased analysis using worldwide arthroplasty registers, the most common causes for revisions in THA were aseptic loosening(55.2%) [2].…”
Section: Introductionmentioning
confidence: 99%